A new variety of Geranium ocellatum (Geraniaceae) from Uttarakhand, India - Hurrah, Imtiyaz Ahmad; Bagri, Ajendra Singh; Singh, Ankit; Wagh, Vijay Vishnu (Phytotaxa, 2022)
A new variety, Geranium ocellatum var. albiflorum, is described here from Tehri district of Uttarakhand state, India. The new variety is readily distinguished from G. ocellatum var. ocellatum by its central white spot at the petal base, dichasial inflorescence and peduncle length. A detailed description, photographs and conservation status are provided for the new variety. A key to the varieties of G. ocellatum is also provided.